Establishment of a novel extracorporeal bowel model to study luminal approaches to treat inflammatory bowel disease - Anne Breitrück; Gisela Sparmann; Steffen Mitzner; Claus Kerkhoff (The Company of Biologists, 2013)
SUMMARY We have established an extracorporeal bowel model system for the analysis of early events in inflammatory bowel disease (IBD) and therapeutic applications. This model consists of an intestinal segment that is cannulated and perfused in situ, allowing the investigation of cellular responses of apical mucosa cells on luminal applied substances. Short-term treatment with iodoacetamide mimicked experimental intestinal inflammation in IBD, as indicated by histological alterations such as hemorrhage, hyperemia and loss of regular crypt architecture, as well as enhanced expression of cytokines (e.g. IL-6, IL-10 and MCP-1) compared with control segments perfused with media. Perfusion of therapeutic agents (e.g. dexamethasone or Mutaflor) in the small intestine segment significantly reduced the features of early inflammation that are induced by iodoacetamide. Moreover, similar data were obtained for Resormin®, a montmorillonite-illite mixed-layer mineral (smectite), indicating that smectites might be a newly identified therapeutic option for IBD. In summary, this model could provide novel insights into epithelial injury as well as genesis of IBD and, therefore, be useful in testing the therapeutic potential of compounds for IBD therapy.